Changes in urinary output due to concomitant administration of sacubitril/valsartan and atrial natriuretic peptide in patients with heart failure: a multicenter retrospective cohort study - Tatsuki Yanagawa; Yuki Asai; Nobuyuki Zakoji; Shingo Hosoe; Yoshihiro Kondo; Shinnosuke Ootsuki; Hidekazu Kato; Maria Aoki; Yoshiaki Yamamoto; Takanori Yamamoto; Masaaki Takahashi (BMC, 2024)
Abstract Background Sacubitril/valsartan is an angiotensin receptor neprilysin inhibitor (ARNI) that inhibits the degradation of endogenous natriuretic peptides. Therefore, ARNIs may increase the efficacy of human atrial natriuretic peptide (hANP), a drug for acute heart failure, by mediating its pharmacological mechanism. This study was aimed at evaluating the effects of ARNIs on the pharmacological effects of hANP by using surrogate marker, such as urinary output, in patients with heart failure. Methods In this multicenter retrospective cohort study, adult patients with heart failure who were taking angiotensin II receptor blockers (ARB) or ARNIs combined with hANP were enrolled. Information on basic characteristics, clinical laboratory data, medical history, and severity of cardiac insufficiency were collected from electronic medical records. The primary outcome was the change in adjusted fluid balance, calculated by IN-volume (mL/day) - OUT-volume (mL/day) / daily hANP dosage (μg). Results Ninety-two and 62 patients in the ARB + hANP and ARNI + hANP groups, respectively, were eligible for analysis. The adjusted fluid balance in the ARNI + hANP group was significantly lower than that in the ARB + hANP group (p = 0.001). After propensity score matching, 27 patients from each group were included. Similarly, there was a significant reduction in adjusted fluid balance in the ARNI + hANP group after propensity score matching (p = 0.026). Conclusions These findings suggest that ARNIs may enhance the efficacy of hANP and the combination of the two may be effective in the treatment of heart failure.